2011
DOI: 10.1016/j.maturitas.2011.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral fractures in women aged 50 years and older with clinical risk factors for fractures in primary care

Abstract: The percentage of previously unknown VFs diagnosed by VFA in women aged 50 years and older with one or more CRFs for fractures in primary care is high. When only using BMD measurements, only half the women eligible for treatment would actually receive this. We recommend performing VFA in all women aged 50 years and older who are referred for DXA based on Dutch case finding criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
1
0
3
Order By: Relevance
“…Therefore, diagnostic discordance is reasonable in terms of a DXA-diagnosed osteoporosis. A Canadian study [ 32 ] reported that adding VFA to BMD altered the diagnostic classification in approximately 1 out of every 5 patients, and a Dutch study [ 33 ] said that adding VFA to BMD increased treatment requirements by 23%. It is crucial to evaluate the treatment requirements of a patient with osteoporosis, whether or not the patient has a fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, diagnostic discordance is reasonable in terms of a DXA-diagnosed osteoporosis. A Canadian study [ 32 ] reported that adding VFA to BMD altered the diagnostic classification in approximately 1 out of every 5 patients, and a Dutch study [ 33 ] said that adding VFA to BMD increased treatment requirements by 23%. It is crucial to evaluate the treatment requirements of a patient with osteoporosis, whether or not the patient has a fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Αντιθέτως, ανάλογη στατιστικά σημαντική εξάρτηση δεν σημειώθηκε ανάμεσα στον αριθμό των οστεοπενικών γυναικών και του επιπολασμού των καταγμάτων της οσφυϊκής μοίρας με βάση τις μετρήσεις στην οσφύ με p-value 0,629 και με βάση τις μετρήσεις στο μηριαίο με p-value 0,292 στο επίπεδο της κάθε μεταβλητής χωριστά. (311,(312)(313)(314)(315)(316)(317)(318)(319)(320)(321)(323)(324)(325)(326). Είναι ενδιαφέρον ότι η μελέτη Tromso αναγνώρισε την ηλικία ως ανεξάρτητο επιβαρυντικό παράγοντα ανάπτυξης σπονδυλικών καταγμάτων σε γυναίκες μέσης ηλικίας, με σχετικό κίνδυνο 1,32 με αύξηση ανά 5ετία 1,32, ενώ το 46% του κινδύνου των σπονδυλικών καταγμάτων θα μπορούσε να αποδοθεί σε ηλικία μεγαλύτερη των 70 ετών (312).…”
Section: λογαριθμιστική συσχέτισηunclassified
“…Η εκτίμηση του BMD έχει αναγνωριστεί ως καθοριστικός παράγοντας κινδύνου για κάταγμα (328). Χαμηλά επίπεδα του BMD και του T-score στην ΟΜΣΣ και στον αυχένα του μηριαίου συνδέονται σημαντικά με την ανάπτυξη σπονδυλικών καταγμάτων (313,317), ενώ η κατάταξη με βάση το BMD που μετρήθηκε στον αυχένα του μηριαίου είχε σημαντικότερη επίδραση ως ανεξάρτητος παράγων για την ανάπτυξη σπονδυλικών καταγμάτων, σε συμφωνία και με τα δικά μας ευρήματα (312,320,326). Η σχετιζόμενη με την ηλικία μείωση στο T-score διαφέρει στις διάφορες ανατομικές σκελετικές θέσεις, με την απώλεια του σπογγώδους οστού να εντοπίζεται μέχρι και στο 50% στους σπονδύλους, προσβάλλοντας κυρίως μετεμμηνοπαυσιακές γυναίκες, ενώ η σχετιζόμενη με την ηλικία απώλεια του οστικού φλοιού προσβάλλει στο 25-40% τον μηριαίο αυχένα (329,330).…”
Section: λογαριθμιστική συσχέτισηunclassified
See 1 more Smart Citation